AKTIVITAS (PLP) DASAR SEBAGAI ALTERNATIF PENGENALAN LINGKUNGAN SEKOLAH DI UPT SPF SD INPRES MINASAUPA - Ahmad Riska Arista; Ratnawati (Jurnal Riset Guru Indonesia, 2024)
The implementation of basic PLP takes place at school offline and on campus online. Basic PLP activities at school are carried out in the form of observation while campus activities are carried out debriefing, reflection and oral exams online or offline. The Basic PLP implementation scheme is carried out with a block system that is traveled for 16 days, 4 days are carried out on campus online or offline and 12 days are carried out at school at school offline with an implementation time of 5 hours 40 minutes per day. Based on the results of observations made in the field introduction activities of UPT SPF SD Inpres Minasaupa, it can be concluded that from the results of practitioner observations regarding the profile there is a school mission, a school organization that includes an organizational structure and the duties and responsibilities of the leadership, as well as human resources in the form of teachers and education personnel, the condition of teachers and the condition of students, there are facilities and infrastructure in schools that are quite adequate. School management UPT SPF SD Inpres Minasaupa, schools play an important role in changing and modifying knowledge in accordance with the needs of students to live in society